Multi-Time Scale Optimal Scheduling of Regional Integrated Energy Systems Considering Integrated Demand Response - Haizhu Yang; Menglong Li; Zhaoyang Jiang; Peng Zhang (IEEE Access, 2020)
The regional integrated energy system (RIES) is an important place for energy development such as multi-energy complementarities and energy Internet, RIES has important application value for realizing sustainable energy development and building a lower-carbon society, the dissipation of renewable energy and the stabilization of load fluctuations have brought challenges to its optimal operation. Integrated demand response (IDR) is detailedly described by price-based and alternative response. Establish a day-ahead and intraday optimization scheduling model considering the demand side response. According to the difference of scheduling time of each energy subsystem of electric, cooling/heating and natural gas, it is divided into three sub-layers of slow control, intermediate control and fast control to perform rolling optimization scheduling. The example analysis shows that the multi-time scale optimization scheduling model can meet the supply and demand balance of the system, and can also restrain the fluctuation of renewable energy and load intraday, improve the stability of the system, and further reduce the operating cost of the system.